PENERAPAN BIMBINGAN KELOMPOK DENGAN PENDEKATAN RATIONAL EMOTIF BEHAVIORIAL THERAPY (REBT) UNTUK MENURUNKAN TINGKAT PROKRASTINASI AKADEMIK SISWA SMK - Tryyani Aprillia; Naning Kurniawati; Vesti Dwi Cahyanigrum (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
Adolescence is a period of change in one's thinking ability. At this time, adolescents are able to think formally - operational, namely a stage of cognitive development that starts at the age of 12 years and continues until adolescence reaches a period of calm or adulthood. Researchers want to test whether the application of group guidance with the REBT approach can reduce the level of academic procrastination? This study uses pre-experiment with one group pretest-posttest design with a sampling technique using purposive sampling. From this study, the results obtained from the pre test obtained from six students concluded that the level of academic procrastination before being given guidance with the REBT technique the average percentage of the six students was 70.46% and was in the high category. Based on the results of the post test on the six students, it can be concluded that the average percentage for the six students is 54.54% and is in the low category. So the research can be concluded by applying group guidance services with effective REBT techniques to help reduce the level of academic procrastination in Trucuk Bojonegoro Vocational High School students.